Annual Report on Exchange Arrangements and Exchange Restrictions 1958. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1958)
This paper analyses relatively little overall progress in the formal relaxation of restrictions. Certainly, progress in this respect was much less than in the immediately preceding years. On the other hand, there was a significant strengthening of most internationally traded currencies, particularly in the opening months of 1958. The rates in free markets began to approximate the rates in official markets. In this respect, there was continued progress toward what is commonly called external convertibility, although the present position still falls short of formal external convertibility. In some countries, restrictions were relaxed to only a limited extent, partly because earlier relaxations had left only restrictions of a protective nature and partly because of the more complex nature of the economic trends which characterized the period. In the light of these trends and, more particularly, of the currency speculation which arose during the middle of the period, it is notable that most countries were able to defend the progress toward freer trade and payments which had been made earlier.